Post-growth and the demand-pull hypothesis of innovation: Biting the hand that feeds you? - Johannes Jasny; Torben Schubert (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
The post-growth discourse emphasizes the role need to limit economic growth as a primary means to stop continuous environmental degradation associated with production induced overexploitation of natural resources. A criticism of the post-growth discourse is, however, that innovation is known to be demand-driven implying that limiting growth may then undermine incentives to innovate. This may reduce the speed with which new environmentally friendly technologies are developed. Empirical analysis of this claim however do not exist. Relying on data from the European Manufacturing Survey 2018 for Germany, we match macroeconomic sector-growth statistics from the German Statistical Office and analyse how firm-level and sector level growth drive firms' innovation activities with a specific focus to environmental innovations. We find that while firm-level growth is strongly associated with all kinds of innovation activities, sector-level growth is not. Our results suggest that limiting overall economic growth may not undermine incentives to innovate as long as growth is still feasible on the level of the firm.
Keywords: 330; Economic growth; Innovation; Post-growth; Demand pull hypothesis; Green growth